Manajemen Vendor Trucking Dalam Pengiriman Barang Ekspor - Cokorda Bagus Purnama Dwisa; Rafi Alfendra; Noorman Irhamna (Institut Transportasi dan Logistik Trisakti, 2019)
This study was conducted at the operational division of PT. DFDS Transport Indonesia. The problem in this study is to know the influence of vendor management to the implementation of export shipping in the operational division. To solve the problem the author used 2 methods. First, the data collection method in the form of questionnaire distributed to 19 respondents with saturated sample techniques used as many as 19 and processed data from the questionnaire. Second, the method of data analysis using regression, correlation analysis, determinant coefficient, and hypothesis testing. The results of the analysis and discussion show that there is a positive influence of vendor management on the export shipping, which is shown by a simple linear line equation, that is; Y = 14.25 + 0.68X, means that every change in one score of variable X will be followed by change in the Y score of 0.68 and a constant value of 14.25. Based on the correlation analysis r = 0.534, it means that there is a moderate influence of variable X on the variable Y. Determination coefficient test shows the number 28.09%, means that the influence of the information system quality to the employee performance is 28.09% while 71.91% is the influence of other factors that were not examined in this study. And the results of the hypothesis test show that tcount = 2.579 and ttable = 1.740 or tcount> ttable then Ho is rejected and Ha is accepted, means that there is a significant influence of vendor management towards the implementation of export shipping.